2006
DOI: 10.17221/5569-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Serum lidocaine concentration after epidural administration in dogs

Abstract: ABSTRACT:The pharmacokinetics of lidocaine deals with the measurement of lidocaine concentration in the blood and its changes over time. The toxicity of lidocaine is a function of its peak plasma concentration, which in turn depends on several factors including total dose and rates of systemic absorption and elimination. The aim of the study was to assess serum levels of lidocaine after a single shot epidural injection in dogs seen in daily practice. The study included nine dogs undergoing different types of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Hence, such cardiac depression, at least in terms of the early phase, is unlikely to have been caused solely by the CEA of lidocaine. Plasma or serum lidocaine concentrations in humans and dogs reach a maximum at 10-15 min after a single epidural administration [17,19]. We did not measure plasma concentrations within 30 min of starting CEA and thus could not determine the maximum plasma concentration.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, such cardiac depression, at least in terms of the early phase, is unlikely to have been caused solely by the CEA of lidocaine. Plasma or serum lidocaine concentrations in humans and dogs reach a maximum at 10-15 min after a single epidural administration [17,19]. We did not measure plasma concentrations within 30 min of starting CEA and thus could not determine the maximum plasma concentration.…”
mentioning
confidence: 97%
“…Loading injections in the MD group involved doses of 4 mg/kg; such doses are widely considered to maintain clinical analgesic effects for approximately 2 hr in dogs under epidural analgesia [9]. Vnuk et al [19] reported that a single epidural injection of 4 mg/kg lidocaine rarely influenced HR and blood pressure in dogs anesthetized with isoflurane. Because our regimen included CEA after a loading injection, our parameters and theirs cannot be directly compared; however, HR and blood pressure in the MD and HD groups decreased rapidly immediately after the loading injection (Fig.…”
mentioning
confidence: 99%
“…A study conducted by Sakonju (15) investigated the effects of continuous epidural administration of lidocaine (3 mg/kg) in dogs anesthetized with isofl urane and they found that HR and MAP signifi cantly decreased immediately after epidural administration of lidocaine. Vnuk et al (16) showed that epidural administration of lidocaine (4 mg/kg) in dogs under isofl urane anesthesia had no signifi cant changes on HR and MAP. In the present study, we observed declines in cardiovascular parameters following the administration of epidural anesthesia.…”
Section: Fig 1 Cortisol Levels In Fentanyl and Lidocaine Groupsmentioning
confidence: 99%
“…On the other hand, absorption of local anaesthetics from the site of infiltration into the systemic circulation could lead to toxic effects, mainly concerning the central nervous system (CNS) (excitation, convulsions, CNS depression and respiratory arrest) and the cardiovascular system (hypotension, arrhythmia, myocardial depression and cardiac arrest) (Liu et al ., ). The degree of toxicity is a function of the peak plasma concentration reached which, in turn, depends on the dose administered, the route of administration, the rate of systemic absorption and the metabolism and elimination of the drug (Vnuk et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…However, Vnuk et al . () pointed out that signs of neurotoxicity of lidocaine might be masked in dogs undergoing general anaesthesia.…”
Section: Introductionmentioning
confidence: 99%